IITA supports the introduction of Semi Autotrophic Hydroponic (SAH) laboratory in Rwanda - International Institute of Tropical Agriculture (Rwanda, 2022)
IITA in Rwanda introduced the Semi Autotrophic Hydroponic (SAH) laboratory at Rwanda Agriculture and Animal Resources Development Board (RAB)- Rubona station, to increase the multiplicative rates while overcoming low survival rates during plantlet acclimatization of cassava seeds.